PENINGKATAN KERJA PADA AIR CONDITIONER DALAM MENJAGA SUHU RUANG AKOMODASI DI MV. GLOVIS DAYLIGHT - Rizqi Aditya Pratama; Dwi Prasetyo (Dinamika Bahari, 2019)
ABSTRACT Cooling machine is one of the auxiliary machineries that works to produce temperatures or cold temperatures to cool the room above the ship and provide a sense of comfort on the crew of the ship. The method used in this study is a qualitative method with the approach of the Fishbone Analysis method, finding the main causes of less optimal Air Conditioner work, finding the impact less optimal work of Air Conditioners as well as combining it with the Fault Tree Analysis method to find the effort of the most basic problems (Basic Event). The results of this study found the main factors that lead to less optimal work of Air Conditioner namely the occurrence of sedimentation on condensor pipes so that it disrupts the condensation process. This is caused by the dirty LTCooler. The impact that occurred was the crew felt uncomfortable when being in one room, resulting in considerable losses both internal and external impacts. Then the efforts made are maintenance of machinery in accordance with the System Maintenance Plan and water testing on LT Cooler